Comparative analysis of the math learning process implementation in perspective of teachers' work period - Pradana, Kenny Candra; Rosidin, Undang; Wijaya, Agung Putra (Universitas Islam Negeri Raden Intan Lampung, 2024)
The role of mathematics teachers in the success of the learning process can be seen from the perspective of the work period, which reflects the level of experience. Therefore, this research aims to analyze the comparison of the implementation of the mathematics learning process from the perspective of the teacher's work period. The type of research carried out in this study is qualitative descriptive research. The subjects in this research were 2 mathematics subject teachers at one of the state junior high schools in South Lampung, with the criteria being 1 junior teacher and 1 senior teacher. Data collection techniques use participant observation, interviews, and documentation. The implementation of the learning process is measured using instruments in the form of observation sheets and interview guides. The observation sheet uses the Guttman scale and the Likert scale. The data analysis technique uses Miles and Huberman's steps, which consist of data collection, data presentation, data reduction, and verification or drawing conclusions. Based on the research results, it was found that both junior and senior teachers had good criteria for implementing the mathematics learning process. So, it can be concluded that differences in teachers’ work periods do not affect the process of implementing mathematics learning. Based on these results, support from the school must play an important role. Both junior and senior teachers must receive sufficient support from school management, continuous training, and guidance so that they can achieve good criteria in implementing the mathematics learning process.